Evaluation of potential RNA‐interference‐target genes to control cotton mealybug, Phenacoccus solenopsis (Hemiptera: Pseudococcuidae). (10th May 2017) - Khan, Arif M.; Ashfaq, Muhammad; Khan, Azhar A.; Naseem, Muhammad T.; Mansoor, Shahid
Abstract: RNA interference (RNAi) of vital insect genes is a potential tool for targeted pest control. However, selection of the right target genes is a challenge because the RNAi efficacy is known to vary among insect species. Cotton mealybug, Phenacoccus solenopsis, is a phloem‐feeding economically important crop pest. We evaluated the RNAi of 2 vital genes, Bursicon ( PsBur ) and V‐ATPase ( PsV‐ATPase ) as potential targets in P. solenopsis for its control. PCR fragments of PsBur and PsV‐ATPase were amplified using cDNA synthesized from the total RNA. The PCR amplicons were cloned into Potato virus X (PVX) to develop recombinant PVX for the inoculation of Nicotiana tabacum plants for bioassays with healthy P. solenopsis . Reverse‐transcription‐polymerase chain reaction (RT‐PCR) was used to validate the expression of transgenes in the recombinant‐PVX‐inoculated plants (treated), and suppression of the target genes in the mealybugs exposed to them. The RT‐PCR confirmed the expression of transgenes in the treated plants. Mealybug individuals on treated plants either died or showed physical deformities. Further, the population of mealybug was significantly reduced by feeding on N. tabacum expressing RNAi triggers against PsBur and PsV‐ATPase . The results conclude that RNAi is activated in P. solenopsis by feeding on N. tabacum expressing RNAi triggering elements of PsBur and PsV‐ATPase genes through recombinant PVX vector. Further, V‐ATPase and Bursicon genes are potential targets for RNAi‐mediated control of P. solenopsis .